Generic Substitution in Malaysia: Recommendations from a Systematic Review - Mohamed Azmi Hassali, Jayabalan Thambyappa, Fahad Saleem, Noman ul Haq, Hisham Aljadhey (Journal of Applied Pharmaceutical Science)
Generic substitution is the act of switching from a branded drug to its therapeutically equivalent generic version. This study aims to systematically review the literature with regards to generic substitution around the globe. Studies compared generic and brand-name drugs for clinical efficacy and cost effectiveness. The current findings show that the new policies are aimed at supporting the development of the generics industry in the respective countries. Further investigation is needed to explore the implementation of the current generic substitution policies and how to increase their accessibility to the general population. Generic substitution policies comparison between countries were conducted among 9 countries, that is, Australia, Canada, Czech Republic, Ireland, Japan, Switzerland, Indonesia, United State and United Kingdom. From 27 journals that were reviewed, only 14 were selected based on the fulfilled criteria appropriate to the journals that we had searched. All these policies were then studied to propose recommendations for generic substitution.
Keywords: Generic substitution guideline, drug policy worldwide, generic drug, pharmaceutical policies, bioequivalent, quality assurance.